Characteristics of consumer terminology for health information retrieval - Zeng, Q; Kogan, S; Ash, N; Greenes, R A; Boxwala, A A (Methods of information in medicine, 2002)
As millions of consumers perform health information retrieval online, the mismatch between their terminology and the terminologies of the information sources could become a major barrier to successful retrievals. To address this problem, we studied the characteristics of consumer terminology for health information retrieval. Our study focused on consumer queries that were used on a consumer health service Web site and a consumer health information Web site. We analyzed data from the site-usage logs and conducted interviews with patients. Our findings show that consumers' information retrieval performance is very poor. There are significant mismatches at all levels (lexical, semantic and mental models) between the consumer terminology and both the information source terminology and standard medical vocabularies. Comprehensive terminology support on all levels is needed for consumer health information retrieval.